Prawda, piękno i dobro w paryskich wykładach Victora Cousina =Truth, beauty and goodness in Victor Cousin`s Paris lectures - Gamrat, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The Platonic triad became the leitmotif of the lectures on the history of philosophy given at the Ecole normale in Paris by one of the most important French philosophers of the first half of the 19th century - Victor Cousin (1792?1867). The lectures given in 1818 were not published in book form until 1836 by Adolphe Garnier.
Keywords: Cousin, Vikcor (1792-1867); triada Platońska; klasyfikacja sztuk; filozofia; literatura; 18 w.; 19 w.; Platonic triad; classification of arts; philosophy; literature